(untitled) (Международный научный журнал «Инженер», 2026)
The article examines transport as a source of environmental pollution. It analyzes the educational process in environmental disciplines at foreign and domestic universities. The teaching methodology of the "Ecology" course is discussed with a focus on shaping an environmentally conscious worldview among future transport industry specialists. The approach considers production-specific factors and aims to foster student interest and creativity through extracurricular activities. Measures are proposed to further improve environmental education by nurturing students’ love for nature, respect for their chosen profession, and a deep understanding of the goals of the "Ecology" discipline. These improvements are to be achieved through enhanced integration between educational institutions and industry.